THE INFLUENCE OF MOTIVATION AND OTHER FACTORS ON THE PERFORMANCE OF PERUM X HEAD OFFICE EMPLOYEES - Tiara Amanda Putri; Syahrian Syahrian (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Employee performance is one very important aspect for a company or organization. Therefore, this study aims to examine the influence between employee performance with motivation, organizational culture, and work discipline on Perum X Head Office employees. This study used a questionnaire to collect data. The sample in this study were 85 employees. The sampling technique in this study used probability sampling method with simple random sampling technique through sample size using slovin formula. The data analysis method used is multiple linear regression. Data is analyzed by testing normality, classical assumptions, model tests, and hypotheses. The results of this research analysis show that motivation has no effect on employee performance while organizational culture, and work discipline affect employee performance. So that Perum X Head Office employees need to pay attention to the level of motivation, organizational culture, and work discipline as an effort to improve employee performance.